CORRECTIVE EFFECT OF LONGITUDINAL RESECTION OF THE STOMACH ON CONCOMIENTED DISEASES ASSOCIATED WITH MORBID OBESITY - Alijon S. Murodov; Oktyabr R. Teshaev; Alimbay Mavlanev (Central Asian Journal of Medicine, 2023)
Studying of the corrective effect of longitudinal gastrectomy on concomitant diseases in patients with morbid obesity. This scientific work is based on the results of a comprehensive examination and treatment of 187 patients with MO who were treated in the our clinical bases from 2021 to 2023. The analysis of comorbidities in the compared groups showed that one or more comorbidities were detected in 52% of the control group, 57.5% of the main group. The main part of these patients was made up of patients with obesity of the III degree. In particular, if in the control and main groups, arterial hypertension was detected in 50 and 59.3% of patients before the surgical procedure, then 3 months after the surgical procedure, an increase in blood pressure was observed in 45.4 and 37% of the patients. After 6 months, this indicator was found in 27.3 and 14.8% of patients, after 12 months - in the control group, it was found in 9.1% of patients, while in the main group, no increase in blood pressure was observed. After surgery, the clinical signs of arterial hypertension and arthralgia in patients with morbid obesity gradually disappeared with the elimination of obesity. In conclusion, these clinical signs were caused by obesity, and its elimination led to the disappearance of these clinical signs.